Storytelling Marketing, Content Marketing, and Social Media Marketing on the Purchasing Decision - Saida Zainurossalamia ZA; Irsan Tricahyadinata; Robiansyah Robiansyah; Dio Caisar Darma; Gusti Noorlitaria Achmad (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The development of technology in the digital age can’t be avoided in today's life. Nowadays social media is increasingly loved by marketers as a tool to introduce or promote their products because of low costs and can reach more audiences. The development of marketing in this digital era shows that consumers not only buy products but the experiences created and the emergence of emotions are also expected by consumers when consuming a product. This study uses multiple linear regression analysis tools and the data used are primary data respondents of users of Shinzu'i UME body mist products. The purpose of this study is to find out whether storytelling marketing, content marketing, and social media marketing have an influence on purchasing decisions of Shinzu'i UME body mist products. The results of this study indicate that storytelling marketing has no effect on purchasing decisions, content marketing has an effect on purchasing decisions, and social media marketing has no influence on purchasing decisions. The low coefficient of determination shown by these three variables in predicting purchasing decisions for Shinzu'i UME body mist products needs to be evaluated in the future.